Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jctb.1545
|View full text |Cite
|
Sign up to set email alerts
|

Efficient phenol removal of wastewater from phenolic resin plants using crosslinked cyclodextrin particles

Abstract: Removal of phenolic compounds from a raw industrial wastewater from phenolic resin processing, of which the components are phenol (8.9 wt%), m-and p-cresols (0.33 wt%), and xylenols (0.044 wt%), was carried out by using crosslinked cyclodextrin particles as a sorbent. A series of sorbents was prepared by varying the combination of cyclodextrin (CyD), β-CyD, γ -CyD, Mix-CyD (α-CyD:β-CyD:γ -CyD:dextrin = 30:10:10:50 wt/wt), the crosslinker, hexamethylene diisocyanate (HDI) or toluene-2,6-diisocyanate, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…In our research in a recent article, 1,2 we carried out an attempt to find a novel cyclodextrin (CyD) polymer for the removal of phenols from raw industrial wastewater discarded from phenolic resin processing, and found that the most efficient removal method was by pulverized crosslinked β-CyD with hexamethylene diisocyanate (HDI) in a 1:8 molar ratio, or pulverized crosslinked Mix-CyD (α-CyD: β-CyD: γ-CyD: dextrin = 30 : 10 : 10 : 50 wt/wt) with HDI, also in a 1:8 molar ratio, with a mean diameter of below 53 μm. However, the types of equipment that can be employed for the removal of pollutants from water are the stirred-tank, fluidized bed, and column.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our research in a recent article, 1,2 we carried out an attempt to find a novel cyclodextrin (CyD) polymer for the removal of phenols from raw industrial wastewater discarded from phenolic resin processing, and found that the most efficient removal method was by pulverized crosslinked β-CyD with hexamethylene diisocyanate (HDI) in a 1:8 molar ratio, or pulverized crosslinked Mix-CyD (α-CyD: β-CyD: γ-CyD: dextrin = 30 : 10 : 10 : 50 wt/wt) with HDI, also in a 1:8 molar ratio, with a mean diameter of below 53 μm. However, the types of equipment that can be employed for the removal of pollutants from water are the stirred-tank, fluidized bed, and column.…”
Section: Introductionmentioning
confidence: 89%
“…With the present [β-CyD/HDI(1/8)]/HDI polymer beads, a two-stage uptake of phenol was observed, while with β-CyD/HDI(1/8) polymer powder only almost instantaneous adsorption reaching equilibrium was observed. 1,2 This behavior seems to be due to both the increase in particle size and the two-layer structures of the polymer beads resulting from the two stages of crosslinking of β-CyD, as shown in Fig. 3 (A): a hard skin layer (outer layer) of poor permeability and a soft core layer (inner layer) of good permeability.…”
Section: Performance Of β-Cyd Polymer Beads In Batchwise Adsorptionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ingestion of such contaminated water in the human body causes protein degeneration, tissue erosion and paralysis of the central nervous system together with damage to the kidneys, liver and pancreas. 13 Water-insoluble β-CD polymer, which is synthesized by crosslinking the hydroxyl groups of β-CD with diisocyanates to form a stable crosslinked network, have already been used by investigators to remove phenol from wastewater, [14][15][16] but little is known about the adsorption kinetics and thermodynamics of the β-CD polymer for phenol.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been carried out on the fabrication of cross-linked ␤-cyclodextrin polymers for the adsorption of phenol (Romo, Penas, Isasi, Garcia-Zubiri, & Gonzalez-Gaitano, 2008;Yamasaki, Makihata, & Fukunaga, 2006). The chemical stability of polystyrene makes it a good support material for ␤-CD and Jiang et al (2006) prepared a novel copolymer via copolymerization of (6-O-butene diacid ester)-␤-cyclodextrin and styrene.…”
Section: Introductionmentioning
confidence: 99%